EVALUASI KAPASITAS STRUKTUR BAWAH JEMBATAN INTEGRAL - Miftah Hadibrata M.; Andi Indianto (Politeknik Negeri Jakarta, 2022)
The construction of integral bridge Overpass Cilenggang 1 on the Serpong – Balaraja Section 1A Toll Road Construction Project was built on soft soil. This evaluation aims to analyze the strength of the integral bridge substructure and justify the strengthening of the substructure if it is not strong enough to withstand the load in accordance with SNI 1725:2016. The evaluation substructure of the integral bridge capacity used SAP2000 software with the load accordance to SNI 1725:2016 for bridge loading. The result of the research show that the capacity of the integral bridge Overpass Cilenggang 1 structure is strong enough to withstand the working load because the reinforcement capacity used for the substructure is stronger than the reinforcement from the result of analysis with SAP2000 software. Based on the result of the research, it can be concluded that the reinforcement used for Overpass Cilenggang 1 substructure is strong enough to withstand the load working on structure and there is no need to justify the reinforcement for the integral bridge substructure. Keywords: Evaluation, Integral Bridge, Load, Reinforcement, Substructure.